A Review of the Use of Strategic Management Tools in the HealthSector - Dani Sahirul Alim; Nur Wening (Indian Journal of Forensic Medicine & Toxicology, 2021)
This paper is a review and study of various research related to tools of strategic, and factors that influenceboth of internal and external strategic in medical facilities research. The purpose of the review is to exploreand connecting theories from various research. This paper identified 51 articles with related topics publishedthe last decade. The results of this study that research related to implementation tools of strategic in healthfacilities still rarely. The use of SWOT (strengths weaknesses opportunities threats) analysis is the mostpopular tool used (42.86%), followed by Break-even analysis (28.56%), Balanced scorecard (BSC) and PEST(political, economic, socio-cultural, technology) each (14.29%). Based on the analysis of environmentalfactors related to internal factors in the health facility amount of 33.33%. External environmental factors inhealth facilities that have been studied amounted to 66.66%. Based on the summary of research related tointernal and external, it is known that industry environment factors and rivalry environment factors are stillrarely studied. The general environmental factors of demography and epidemiology are still rare studies andhave the opportunity to be researched and developed.